PENANAMAN NILAI KARAKTER JUJUR DAN DISIPLIN PADA SISWA KELAS 1 MELALUI PEMBIASAAN HARIAN DI UPT SPF SD NEGERI 107405 SEI ROTAN - Rizky Seni Utami; Wariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of honesty and discipline character values among first-grade students through daily habituation activities at UPT SPF SD Negeri 107405 Sei Rotan, as well as to identify the supporting factors, inhibiting factors, and the impacts resulting from the implementation of the program. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, first-grade teacher, first-grade students, and several parents. Data were collected through observation, interviews, and documentation.Data validity was ensured through source triangulation, technique triangulation, and time triangulation. The results revealed that the cultivation of honesty and discipline character values was implemented through various daily habituation activities, such as arriving at school on time, lining up before entering the classroom, greeting teachers, praying before and after lessons, maintaining classroom cleanliness, completing assignments on time, and encouraging students to speak and act honestly in their daily lives. The success of the program was supported by teachers’ role modeling, the principal’s support, and collaboration between the school and parents. The inhibiting factors included differences in students’ family backgrounds and varying levels of character understanding among students. The implementation of daily habituation activities had positive impacts on students’ character development, as evidenced by increased honesty in admitting mistakes and conveying truthful information, as well as improved discipline in obeying school rules, participating in learning activities, and completing assignments responsibly. Therefore, daily habituation activities proved to be an effective strategy for instilling honesty and discipline character values in elementary school students and supporting the development of a positive school culture.